The Impact of an Integrated Care Management Program on Acute Care Use and Outpatient Appointment Attendance Among High‐Risk Patients With Lupus. Issue 4 (18th January 2022) - Williams, Jessica N.; Taber, Kreager; Huang, Weixing; Collins, Jamie; Cunningham, Rebecca; McLaughlin, Katherine; Vogeli, Christine; Wichmann, Lisa; Feldman, Candace H.
Abstract : Objective: Patients with systemic lupus erythematosus (SLE) often struggle with high acute care use (emergency department [ED] visits and hospitalizations) and missed appointments. A nurse‐led integrated care management program (iCMP) at our multihospital system coordinates care for patients at high risk for frequent acute care use due to comorbidities, demographics, and prior use patterns. We studied whether iCMP enrollment was associated with decreased acute care use and missed appointment rates among patients with SLE. Methods: We used a validated electronic health record (EHR) machine learning algorithm to identify adults with SLE and then determined which patients were enrolled in the iCMP from January 2012 to February 2019. We then used EHR data linked to insurance claims to compare the incidence rates of ED visits, hospitalizations, potentially avoidable ED visits and hospitalizations, and missed appointments during iCMP enrollment versus the 12 months prior to iCMP enrollment. We used Poisson regression to compare incidence rate ratios (IRRs) during the iCMP versus pre‐iCMP for each use measure, adjusted for age, sex, race and ethnicity, number of comorbidities, and calendar year, accounting for within‐patient clustering. Results: We identified 67 iCMP enrollees with SLE and linked EHR claims data. In adjusted analyses, iCMP enrollment was associated with reduced rates of ED visits (IRR 0.63, 95% confidence interval [CI] 0.47‐0.85), avoidable ED visits (IRR 0.50, 95% CI 0.28‐0.88), and avoidable hospitalizations (IRR 0.37, 95% CI 0.21‐0.65). Conclusion: A nurse‐led iCMP was effective at decreasing the rate of all ED visits and potentially avoidable ED visits and hospitalizations among high‐risk patients with SLE. Further studies are needed to confirm these findings in other patient populations.